2005
DOI: 10.1038/nm1234
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β protein immunotherapy neutralizes Aβ oligomers that disrupt synaptic plasticity in vivo

Abstract: One of the most clinically advanced forms of experimental disease-modifying treatment for Alzheimer disease is immunization against the amyloid beta protein (Abeta), but how this may prevent cognitive impairment is unclear. We hypothesized that antibodies to Abeta could exert a beneficial action by directly neutralizing potentially synaptotoxic soluble Abeta species in the brain. Intracerebroventricular injection of naturally secreted human Abeta inhibited long-term potentiation (LTP), a correlate of learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
349
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(367 citation statements)
references
References 29 publications
14
349
1
3
Order By: Relevance
“…[21][22][23] Because immunotherapeutic strategies displayed great promise in animal models of AD, a strong effort was made by the industry to inhibit generation of toxic Ab aggregates and remove soluble and aggregated Ab deposited in the brains of AD patients by both active and passive anti-Ab immunotherapy strategies. [24][25][26][27][28][29][30][31] Data from active vaccine trials indicate that, to be effective, anti-Ab therapeutic should induce high titers of anti-Ab antibodies without activation of autoreactive T cells.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Because immunotherapeutic strategies displayed great promise in animal models of AD, a strong effort was made by the industry to inhibit generation of toxic Ab aggregates and remove soluble and aggregated Ab deposited in the brains of AD patients by both active and passive anti-Ab immunotherapy strategies. [24][25][26][27][28][29][30][31] Data from active vaccine trials indicate that, to be effective, anti-Ab therapeutic should induce high titers of anti-Ab antibodies without activation of autoreactive T cells.…”
Section: Introductionmentioning
confidence: 99%
“…One potentially powerful strategy for reducing the level of Aβ in the brain is immunotherapy, in which antibodies specific to Aβ facilitate the clearance of amyloid deposits [10][11][12][13][14][15][16][17][18]. The first human AD vaccine consisted of fibrillar Aβ 42 formulated in QS21 adjuvant (AN-1792 trial) that induced strong Th1-type anti-Aβ immune responses [19], even in Th2-prone BALB/c mice [20].…”
Section: Introductionmentioning
confidence: 99%
“…This AN-1792 clinical trial was halted due to the development of meningoencephalitis in a small proportion of the subjects [21][22][23][24][25][26], but follow up studies have demonstrated that strong anti-Aβ antibody responses specific to the linear Aβ [1][2][3][4][5][6][7][8] peptide [27] in some patients reduced AD pathology and diminished the cognitive decline associated with the disease [24,[27][28][29][30][31][32][33]. These data along with preclinical studies demonstrated that anti-Aβ antibodies directed to N-terminal region of Aβ 42 are effective in clearance of amyloid plaques [16,34,35]. On the contrary, the strong autoreactive Th1-type response specific to Aβ is thought to underlie the development of meningoencephalitis observed in the AN-1792 trial [30,31,33].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the evidence that oligomeric Aβ42 is the most toxic species of Aβ is convincing. Studies strongly support the following: 1) all else being equal, enriched oligomeric preparations of Aβ42 appear to be the most toxic species [38,39]; 2) oligomeric species of Aβ42 can inhibit long term potentiation (LTP) and lead to synaptic dysfunction [48,49]; 3) memory loss occurs prior to extensive deposition of fibrillar Aβ42 in transgenic mice and can be reversed by targeting soluble species of Aβ42 [50,51,52,53]; and 4) oligomeric Aβ42 species exist in AD brain [54]. However, it is important to appreciate that the removal or reduction of the soluble, toxic oligomeric forms of Aβ42 from brain parenchyma will require the concomitant reduction and removal of the insoluble (fibrillar) Aβ42 pool as well.…”
Section: Potential Uses Of An Aβ Imaging Agentmentioning
confidence: 94%
“…In Tg2576 mice, no obvious correspondence between memory and insoluble Aβ levels was apparent [53]. Furthermore, passive immunization studies of this same Tg2576 strain of mice showed that memory deficits and disruption of LTP can be reversed without affecting the levels of soluble or insoluble Aβ, suggesting "neutralization" of soluble Aβ by antibodies may be sufficient to aid in cognitive improvement [51,52]. These results were interpreted to imply that insoluble Aβ is a surrogate marker for "small assemblies" of Aβ that disrupt cognition and occur as intermediates during the formation of insoluble Aβ.…”
Section: Potential Uses Of An Aβ Imaging Agentmentioning
confidence: 98%